Effectiveness of oral health education among primary health care workers at the primary health center in Nellore district, Andhra Pradesh - Muthyala Pavana Sandhya; M Shanthi; Nusrath Fareed; K M Sudhir; R.V.S Krishna Kumar (Wolters Kluwer Medknow Publications, 2014)
Background: Primary dental care can be a way of achieving good oral health for the community. This can be achieved by integration of oral health care with the existing primary health care activities through training of primary health care workers on aspects of oral health. Objective: To assess the effectiveness of oral health education among primary health care workers at the primary health center (PHC) in Nellore district, Andhra Pradesh. Materials and Methods: Descriptive longitudinal study was conducted from June 2010 to August 2010 at a PHC. Knowledge about oral health among primary health care workers was pretested using a self-administered questionnaire prepared in local language (Telugu). Later after a month health education was provided to the health workers, and pamphlets with information on oral health were distributed. Posttest assessment was done 1-month after providing health education using the same questionnaire. Statistical analysis was performed using the SPSS 12.0 software, Student's t-test was used to compare knowledge scores between pre and posttests. Results: A total of 118 Primary Health Care Workers with the majority in the 20-30 years age group participated in the study. Posttest assessment showed a change in knowledge level with an overall increase in knowledge level of primary health care workers with a mean difference of 12.56 ± 3.23, which was highly significant (P < 0.001). Conclusion: The knowledge about oral health was poor, and it improved after providing health education to primary health care workers. Change in knowledge was appreciable and may play a key role in oral health promotion of the vast majority of the rural population.